2016
DOI: 10.3389/fmicb.2016.00572
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Epimerization as a Route for Deoxynivalenol Detoxification: the Influence of Growth and Environmental Conditions

Abstract: Deoxynivalenol (DON) is a toxic secondary metabolite produced by several Fusarium species that infest wheat and corn. Food and feed contaminated with DON pose a health risk to both humans and livestock and form a major barrier for international trade. Microbial detoxification represents an alternative approach to the physical and chemical detoxification methods of DON-contaminated grains. The present study details the characterization of a novel bacterium, Devosia mutans 17-2-E-8, that is capable of transformi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 54 publications
2
56
0
Order By: Relevance
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…A number of studies have evaluated intrinsic factors, including carbon source [26,34], nitrogen source [26,34,88], vitamins [26], metals ions [12,34,46,89,90,91,92,93], enzyme inhibitors and promoters [52,89,90,91,92,93,94], initial concentration of mycotoxins [93,95], initial concentration of cells [53,95] and initial pH value [12,14,17,26,31,34,41,46,54,60,88,89,95,96], as well as extrinsic factors, including temperature [12,14,17,25,26,31,34,38,41,46,52,54,60,88,89,95,96], aeriation (shaking rate) [26], oxygen preference [14], as well as pre-incubation [26] and incubation time [34,97]. The experimental designs and optimized biotransformation conditions are summarized in Table 2.…”
Section: Strategies and Methodologiesmentioning
confidence: 99%
“…It was reported that Devosia mutans 17‐2‐E‐8 had the capacity to transform DON at rates close to 0·3 μ g h −1 per 10 7 cells with its exponential growth phase (He et al . ). It appears that DON‐transformation efficiency of strain DDB001 (6·8 μ g h −1 per 10 7 cells) is higher than that of strain 17‐2‐E‐8.…”
Section: Resultsmentioning
confidence: 97%
“…(2015) and He et al. (2016) observed that Devosia mutans 17‐2‐E‐8 from soil completely converted DON into the major metabolite 3‐keto‐DON and the secondary metabolite 3‐epi‐DON under aerobic conditions. Carere, Hassan, Lepp, and Zhou (2018) and Hassan et al.…”
Section: Degradation Of Don By Microorganismsmentioning
confidence: 97%
“…Paenibacillus polymyxa also inhibited the growth of F. graminearum and the production of DON under greenhouse conditions (He, Boland, & Zhou, 2009). He et al (2015) and He et al (2016) observed that Devosia mutans 17-2-E-8 from soil completely converted DON into the major metabolite 3-keto-DON and the secondary metabolite 3-epi-DON under aerobic conditions. Carere, Hassan, Lepp, and Zhou (2018) and Hassan et al (2017) investigated the relevant enzymatic mechanism underlying epimerization.…”
Section: Bacteria From Soilmentioning
confidence: 99%